2007
DOI: 10.1001/archopht.125.3.340
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Visual Function Abnormalities Using the Swedish Interactive Threshold Algorithm and Matrix Perimetry in Eyes With Glaucomatous Appearance of the Optic Disc

Abstract: To compare the ability of 24-2 frequencydoubling perimetry (FDP-Matrix) with standard automated perimetry with the Swedish interactive threshold algorithm (SAP-SITA) in detection of visual function abnormalities in patients with glaucomatous-appearing optic discs (GAOD). Methods: This observational case-control study included 80 patients with GAOD and 54 control subjects diagnosed by masked assessment of optic disc stereoscopic photographs. Abnormal visual function at SAP-SITA and FDP-Matrix testing required c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…21 The location of defects within 12 hemifield clusters found with FDT agreed moderately well with those detected with SAP (kappa=0.48). Sakata et al 22 used the same criteria as in our study for definition of abnormal visual field and reported a moderate agreement between the two perimetric methods similar to our finding (κ=0.49). The moderate agreement between these two tests might be again explained by the different psychophysical properties and algorithms used in these tests.…”
Section: Y›lmaz Et Al Comparison Of Humphrey Matrix and Sap-sitasupporting
confidence: 88%
“…21 The location of defects within 12 hemifield clusters found with FDT agreed moderately well with those detected with SAP (kappa=0.48). Sakata et al 22 used the same criteria as in our study for definition of abnormal visual field and reported a moderate agreement between the two perimetric methods similar to our finding (κ=0.49). The moderate agreement between these two tests might be again explained by the different psychophysical properties and algorithms used in these tests.…”
Section: Y›lmaz Et Al Comparison Of Humphrey Matrix and Sap-sitasupporting
confidence: 88%
“…Thus the test duration, here about 2.5 min/eye including time for rests between segments, is quite short; especially for patients for whom the typical SITA test duration is 6 min/eye or more. 15,33,34 Our more recent studies have indicated that mfPOP employing between 40 and 60 stimulus regions/eye may be practical. 24 The use of dichoptic stimuli means that efferent and afferent defects can often be differentiated on a region-byregion basis.…”
Section: Discussionmentioning
confidence: 99%
“…Visual function abnormality was determined by comparing the visual field results against the commercial available normative database of each test, and the criteria used was based on glaucoma hemifield test result outside normal limits, pattern standard deviation less than 5% and/or the presence of a cluster of three or more abnormal points (P < 5% with at least one point P < 1%) on the pattern deviation probability plot. This study also required confirmation of visual function abnormality in two visual field exams [44 ]. It was observed that FDP-Matrix detected abnormal visual function in more glaucomatous appearing optic disc eyes than SAP-SITA (although this difference was not significant).…”
Section: Frequency-doubling Technology Perimetrymentioning
confidence: 94%
“…Sakata et al [44 ] evaluated the performance of 24-2 FDP-Matrix and SITA-SAP in diagnosing patients with glaucomatous appearing optic disc. Visual function abnormality was determined by comparing the visual field results against the commercial available normative database of each test, and the criteria used was based on glaucoma hemifield test result outside normal limits, pattern standard deviation less than 5% and/or the presence of a cluster of three or more abnormal points (P < 5% with at least one point P < 1%) on the pattern deviation probability plot.…”
Section: Frequency-doubling Technology Perimetrymentioning
confidence: 99%
See 1 more Smart Citation